Penyelenggaraan Vaksinasi Gratis bagi Kelompok Rentan di 6 Kelurahan di Praya, Lombok Tengah - Andini, Dwi Tesna; Imam, Sadrul; Sunni, M. Abdurrahman; Tamim, Muhammad Husni; Islami, Anggun Variasi (Lembaga Yasin AlSys, 2022)
The existence of a world disaster called Corona Virus Disease 2019 (Covid-19) which still exists recently. This virus makes many changes to the world. When the virus first appearance, the people panic about it and now is has started normal since the vaccine program was implemented. From there, the international community began massively implementing vaccines to fight the effects of Covid-19, including Indonesia, which had recorded high transmission of Covid-19. One of the community services being carried out to prevent Covid-19 is by holding free vaccinations for vulnerable communities. The total data on vaccine recipients is 834 people organized by Filantropi Indonesia in collaboration with Non-Governmental Organizations in West Nusa Tenggara. The conclusion of this article is that there has been an increase in the number of people receiving vaccination services.